The Sense of Loss in Jean Rhy’s Voyage in The Dark: The Absence of Mother and Imagined Black Identity - Rarastesa, Zita (UI Scholars Hub, 2015)
The sense of loss of a mother leads Anna Morgan to her imagined black identity. Being a Creole from Dominica, Morgan is alienated both in her home country and in London. Du Bois’s notion of double consciousness substantiates Morgan’s sense of alienation. The racial issue here is not only socially constructed, but it is also personally constructed, as Morgan does not consider England as her homeland although she is as white as English people. people. The character is struggling from identity conflict, as she internalizes the impact of the British colonialization to the black people in Dominica. She feels more black than white because of the image of blackness that she creates from the image of her mother and black women in general, as nurturing, warm and domestic. In addition to that, the geographic location contributes to Morgan’s sense of loss.